Explaining the interaction of mangiferin with MMP-9 and NF-ƙβ: a computational study - Gálvez-Rodríguez, Andy; Ferino-Pérez, Anthuan; Rodríguez-Riera, Zalua; Rodeiro Guerra, Idania; Řeha, David; Minofar, Babak; Jáuregui-Haza, Ulises J (Journal of molecular modeling, 2022)
Mangiferin is a glycosylated xanthone widely distributed in nature, which exhibits wide pharmacological activities, highlighting its anti-cancer properties. Mangiferin interferes with inflammation, lipid, and calcium signaling, which selectively inhibits multiple NFkB target genes as interleukin-6, tumor necrosis factor, plasminogen, and matrix metalloproteinase, among others. In this work, the interactions of this polyphenol with MMP-9 and NF-κβ are characterized by using computational chemistry methods. The results show MMP-9 inhibition by mangiferina is characterized for the interact with the catalytic Zn atom through a penta-coordinate structure. It is also demonstrated through a strong charge transfer established between mangiferin and Zn in the QM/MM study. Concerning the mangiferin/NF-κβ system, the 92.3% of interactions between p50 sub-unity and DNA are maintained with a binding energy of - 8.04 kcal/mol. These findings indicate that mangiferin blocks the p50-p65/DNA interaction resulting in the loss of the functions of this hetero-dimeric member and suggesting inhibition of the cancer progression. Experimental results concerning the anti-cancer properties of mangiferin show that this natural compound can inhibit selectively MMP-9 and NF-ƙβ. Although the anti-tumor properties of mangiferin are well defined, its molecular mechanisms of actions are not described. In this work, a computational study is carried out to characterize the interactions of mangiferin with these molecular targets. The results obtained corroborate the anti-proliferative and anti-apoptotic activity of mangiferin and provide a depiction of its mechanisms of action.
Keywords: Xanthones; xantony; NF-kappa B; TNF-alfa; matrixová metaloproteinasa 9; Tumor Necrosis Factor-alpha; Matrix Metalloproteinase 9